Interfacial engineering enables Bi@C-TiOx microspheres as superpower and long life anode for lithium-ion batteries. (September 2018) - Huang, Zhen-Dong; Lu, Hao; Qian, Kun; Fang, Yan-Wu; Du, Qing-Chuan; He, Yan-Bing; Masese, Titus; Yang, Xu-Sheng; Ma, Yan-Wen; Huang, Wei
Abstract: Bismuth (Bi), a uniquely stable pnictogen element, is deemed a promising anode material for lithium-ion batteries owing to its high volumetric capacity, moderate operating voltage and environmental friendliness. However, the application of Bi as anode is hindered by its low conductivity and large volume change during cycling. Herein, we introduce an advanced surface engineering strategy to construct Bi@C-TiO x microspheres encapsulated by ultra-large graphene interfacial layer. Ultrafine Bi nanoparticles are confined and uniformly dispersed inside the C-TiO x matrix, which is the pyrolysis derivative of the newly developed Bi-Ti-EG bimetal organic frameworks, with the aid of a selective graphene interfacial barrier. A three-dimensional (3D) long-range conductive network is successfully constructed by the ultra-large graphene and the carbonized derivative of Bi-Ti-EG. Additionally, the 3D carbon network and the in-situ formed TiO x coupled with a porous structure act as soft buffer and hard suppressor to alleviate the huge volume change of Bi during cycling, and they also are the important electrochemically active components. Thanks to the synergistic effects intrigued by the aforementioned interfacial engineering strategy, the newly developed ultra-large graphene encapsulated Bi@C-TiO x microspheres exhibit an exceptional superpower and outstanding cycle stability (namely, 333.3, 275 and 225 mAh g −1 at 1, 5 and 10 A g −1, respectively, with remarkable capacity retention upon 5000 cycles), surpassing other reported Bi-based anode materials so far. This study underpins that the nanoscale surface design of electrode materials for batteries is an effective approach to significantly enhance the power capability, capacity and cyclic stability of new metal anodes. Graphical abstract: Thanks to the synergistic effect of ultrafine Bi particles, three-dimensional (3D) long-range conductive network and inner stress alleviation strategy intrigued by the interfacial engineering strategy, the newly developed ultra-large graphene encapsulated Bi@C-TiO x microspheres exhibit an exceptional superpower and outstanding cycle stability. fx1 Highlights: A Bi-Ti-Ethylene glycol bimetal-organic framework is newly developed. A graphene interfacial layer is introduced to enable the formation of Bi@C-TiO x . 3D long-rang conductive network and all-round stress alleviator are built. Superior power and cyclic stability are achieved by graphene wrapped Bi@C-TiOx .